Effect of Ramped Wall Temperature on Unsteady Mixed Convection Flow of Rotating Second Grade Fluid in Porous Medium - Ahmad Qushairi, Mohamad; Khan, Ilyas; Nor Athirah, Mohd Zin; Zulkhibri, Ismail; Sharidan, Shafie (UTM Press, 2016)
The effects of ramped wall temperature, rotation and porosity on mixed convection flow of incompressible second grade fluid are studied. The momentum equation is modelled in a problem of rotating fluid with constant angular velocity subjected to initial and oscillating boundary conditions. The energy equation is also introduced. Some suitable nondimensional variables are used to write equations into non-dimensional form. Laplace transform method is used to solve these equations in order to obtain the analytical solutions of velocity and temperature profiles. Computations are carried out and presented graphically to analyse the effect of second grade fluid parameter, rotation parameter, porosity parameter, Prandtl number and Grashof number on the profiles. It is found that, for larger values of porosity parameter, the fluid velocity will increase for both primary and secondary velocities. The results also show that, velocity and temperature for ramped wall temperature are lower compared to isothermal temperature. It is worth to mention that, the exact solutions obtained in this study can be used to check correctness of the results obtained through numerical schemes.